Histone variant H2A.Z deposition and acetylation directs the canonical Notch signaling response. Issue 16 (9th July 2018) - Giaimo, Benedetto Daniele; Ferrante, Francesca; Vallejo, Diana M; Hein, Kerstin; Gutierrez-Perez, Irene; Nist, Andrea; Stiewe, Thorsten; Mittler, Gerhard; Herold, Susanne; Zimmermann, Tobias; Bartkuhn, Marek; Schwarz, Peggy; et al.
Abstract: A fundamental as yet incompletely understood feature of Notch signal transduction is a transcriptional shift from repression to activation that depends on chromatin regulation mediated by transcription factor RBP-J and associated cofactors. Incorporation of histone variants alter the functional properties of chromatin and are implicated in the regulation of gene expression. Here, we show that depletion of histone variant H2A.Z leads to upregulation of canonical Notch target genes and that the H2A.Z-chaperone TRRAP/p400/Tip60 complex physically associates with RBP-J at Notch-dependent enhancers. When targeted to RBP-J-bound enhancers, the acetyltransferase Tip60 acetylates H2A.Z and upregulates Notch target gene expression. Importantly, the Drosophila homologs of Tip60, p400 and H2A.Z modulate Notch signaling response and growth in vivo . Together, our data reveal that loading and acetylation of H2A.Z are required to assure tight control of canonical Notch activation.